Islam a novel about the Islamic world based on a true story a novel - Dubois, Caroline
1941. Nazi-occupied Bosnia. A Jewish family manages to escape the transport to Auschwitz. With nowhere to hide, they resort to a Muslim woman whom the family knew before the war. At night, the frightened gaunt figures knock on the woman's door. Based on a true story of the life of Zaynab Hardaga, recognized by the Holocaust Muesuem of Israel as Righteous Among the Nations